Microgrids for rural areas : research and case studies (Institution of Engineering and Technology, 2020)
This book focuses on the challenges of rural electrification, particularly in poorer regions. It covers low voltage DC distribution system for various applications including charging of electric vehicles (EV).
Keywords: Microgrids (Smart power grids); Rural electrification.; elektronické knihy; electronic books